1994
DOI: 10.1161/01.cir.89.6.2852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term monotherapy with enalapril, metoprolol, and digoxin on the progression of left ventricular dysfunction and dilation in dogs with reduced ejection fraction.

Abstract: In dogs with reduced LVEF, long-term therapy with enalapril or metoprolol prevents the progression of LV systolic dysfunction and LV chamber dilation. Therapy with digoxin maintains LV systolic function but does not prevent progressive LV enlargement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
86
1
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(103 citation statements)
references
References 38 publications
14
86
1
2
Order By: Relevance
“…Consistent with earlier studies from our laboratory (18,20,24), results of the present study indicate that, in the absence of any therapeutic intervention, progressive deterioration of LV systolic function and chamber remodeling occur in dogs with moderate HF, secondary to loss of viable myocardium. The present study demonstrates that long-term monotherapy with high-dose but low-dose selective MMP inhibitor PG-530742 prevents progressive LV dysfunction and LV chamber remodeling in dogs with moderate HF.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with earlier studies from our laboratory (18,20,24), results of the present study indicate that, in the absence of any therapeutic intervention, progressive deterioration of LV systolic function and chamber remodeling occur in dogs with moderate HF, secondary to loss of viable myocardium. The present study demonstrates that long-term monotherapy with high-dose but low-dose selective MMP inhibitor PG-530742 prevents progressive LV dysfunction and LV chamber remodeling in dogs with moderate HF.…”
Section: Discussionsupporting
confidence: 92%
“…31 Thus, new therapies must be developed to overcome the poor prognosis of MI. Several alternative strategies based on drug treatments, 32 injections of stem cells or proteins, 4,5 surgical interventions 33 and epicardial restraint devices 34 have been used to regenerate the infarcted heart. The effects of liraglutide have been shown to be beneficial for the treatment of MI.…”
Section: Discussionmentioning
confidence: 99%
“…Digitalis traditionally has been used to manage supraventricular tachyarrhythmias14 and dilated cardiomyopathy in dogs,14, 15, 16 but evidence for clinical efficacy is sparse. A positive effect on left ventricular systolic function was identified in digoxin‐treated dogs with experimentally decreased left ventricular ejection fraction,17 and in a small retrospective study of dogs with idiopathic DCM receiving digoxin, decreased heart rate was identified with less pronounced benefit on left ventricular fractional shortening 18. Pimobendan, a calcium‐sensitizing drug with both inotropic and vasodilatory properties, is commonly used to manage CHF in dogs with MMVD and DCM 19, 20.…”
mentioning
confidence: 99%